Catalytic conversion of glycerol to value-added acetol and propylene glycol - Mohamad, Mohd Hanif (2013)
Glycerol conversion to value-added product, acetol was studied through dehydration reaction of glycerol catalyzed by copper chromite in a single step reactive distillation. The physical properties of the synthesized acetol such as its appearance, density and viscosity were compared with those of a commercial product. The effects of reaction temperature, reaction period, catalyst loading and water content in glycerol feedstock were studied to optimize its production. The results showconversion of glycerol increased with the increase of reaction period and catalyst loading while the presence of water in glycerol feedstock decreases the conversion and also reduces the residue which provides ease removal and recycles the catalyst. Optimum conditions for the conversion of glycerol to acetol was at reaction period of 3.5 hours with 2.5% catalyst concentration and 200°C reaction temperature without dilution where the 64.47% product was obtained. Fourier-Transform infrared (FTIR), gas chromatography (GC), gas chromatographymass spectroscopy (GC/MS) and nuclear magnetic resonance (NMR) were used to characterize and validate the product from the dehydration reaction of glycerol. The IR spectrum of product showed stretching of carbonyl group suggested that acetol has been successfully synthesized. The GC-MS analysis showed the value expected for the molecular ion of isolated acetol. The NMR was also used to validate the number and position of carbon and hydrogen in the product by evaluates the chemical shifts. In brief, the synthesis of propylene glycol from acetol and glycerol has successfully been carried out through hydrogenation reaction catalyzed by copper chromite catalyst. Acetol produces the highest conversion to propylene glycol with 88.43% conversion and 65.22% product yield in 24 hours reaction period, 5% catalyst concentration and 200 psi hydrogen pressure at 200°C reaction temperature respectively. Meanwhile, the propylene glycol produces from glycerol yield 61.80% product with the conversion percentage of 72.77% at the same reaction conditions.